Protection of Children as Victims of Domestic Sexual Violence - Simatupang, Nursariani; Faisal, Faisal (International Journal Reglement & Society (IJRS), 2020)
Many parents let their children swallow the bitter pill because of their lecherous act. They make their children victims of sexual violence, regardless of the future of the next child. Sexual violence against children results in children going through life with physical impacts and trauma that have terrible, long-lasting, and even very difficult to get rid of. This study aims to analyze the factors and consequences that arise and to analyze the protection given to children as victims of sexual violence in the household. This research is a normative juridical research. The factors that cause children to become victims of sexual violence, among others, are for the interest of studying black magic and because the perpetrator's wife is no longer able to meet their biological needs. The consequence that arises in the child is that the child experiences trauma and is very disturbed psychologically. The protection provided for children is legal assistance, counseling services, health examination services, and monitoring services. In addition, according to Law Number 17 of 2016 the perpetrator is subject to criminal sanctions, given chemical castration, installation of electronic detectors, and rehabilitation.